Kompetencje nauczycieli w zakresie korzystania z technologii informacyjno-komunikacyjnej w nauczaniu. Z badań etno-pedagogicznych = The teachers` competences in using information and communication technology. From etno-pedagogical research - Gołębniak, Bogusława Dorota; Ostoja-Solecka, Katarzyna (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article discusses cultural contexts of forming teachers? competences in information and communication technology. Based on the results of the studies carried out with the use of educational ethnography (participant observation, interviews, performance), which studies identify barriers in reaching in everyday school reality for new technologies allowing changes (following the schema of "from passing knowledge to constructing knowledge") in the teaching model, the authors of this article suggest solutions in the form of interventional participant study.
Keywords: kompetencje nauczycieli; technologie informacyjno-komunikacyjne; miejsce uczenia (się); wspólnoty uczących (się); rytuały; zmiana; teachers` competences; information and communication technologies; learning place; rituals; change